Dovish coos or hawkish screech? From central bank talk to economic walk - Kerstin Bernoth (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
This paper investigates the effectiveness of the European Central Bank's (ECB) communication in shaping market expectations and real economic outcomes. Using a transformer-based large language model (LLM) fine-tuned to ECB communication, the tone of monetary policy statements from 2003 to 2025 is classified, constructing a novel ECB Communication Stance Indicator. This indicator contains forward-looking information beyond standard macro-financial variables. Identified communication shocks are distinct from monetary policy and central bank information shocks. A structural Bayesian VAR reveals that hawkish communication signals favorable economic prospects, raising output, equity prices, and inflation, but also increases bond market stress. These findings highlight communication as an independent and effective tool of monetary policy, while also underscoring the importance of carefully calibrating tone to balance market expectations, and financial stability.
Keywords: C32; E43; E47; E52; E58; 330; Monetary Policy; Central Bank Communication; Text Sentiment; Transformer-based Large Language Model; Bayesian Vector Autoregression; Local Projections